Phase 1/2 study of cyclin-dependent kinase (CDK)4/6 inhibitor palbociclib (PD-0332991) with bortezomib and dexamethasone in relapsed/refractory multiple myeloma. Issue 12 (2nd December 2015) - Niesvizky, Ruben; Badros, Ashraf Z.; Costa, Luciano J.; Ely, Scott A.; Singhal, Seema B.; Stadtmauer, Edward A.; Haideri, Nisreen A.; Yacoub, Abdulraheem; Hess, Georg; Lentzsch, Suzanne; Spicka, Ivan; Chanan-Khan, Asher A.; et al.
Abstract : This phase 1/2 study was the first to evaluate the safety and efficacy of the cyclin-dependent kinase (CDK) 4/6–specific inhibitor palbociclib (PD-0332991) in sequential combination with bortezomib and dexamethasone in relapsed/refractory multiple myeloma. The recommended phase 2 dose was palbociclib 100 mg orally once daily on days 1–12 of a 21-day cycle with bortezomib 1.0 mg/m 2 (intravenous) and dexamethasone 20 mg (orally 30 min pre-bortezomib dosing) on days 8 and 11 (early G1 arrest) and days 15 and 18 (cell cycle resumed). Dose-limiting toxicities were primarily cytopenias; most other treatment-related adverse events were grade ≤ 3. At a bortezomib dose lower than that in other combination therapy studies, antitumor activity was observed (phase 1). In phase 2, objective responses were achieved in 5 (20%) patients; 11 (44%) achieved stable disease. Biomarker and pharmacodynamic assessments demonstrated that palbociclib inhibited CDK4/6 and the cell cycle initially in most patients.